Revitalization of Titi Papan Station: A High-Tech Architecture Approach to Integrating Heritage and Modernity - Novrial, Novrial; Khodijah , Siti (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
Revitalization of the Titi Papan Station building located in Titi Papan, Medan Deli sub-district, Medan City, is designed for the development of national railways which is scheduled until 2030. Titi Papan Station is one of the stations located on the Medan-Belawan crossing with inactive status. In addition, Titi Papan Station is one of the cultural heritage buildings from the Dutch colonial era that needs to be preserved by revitalizing the building because physically the Titi Papan Station building is no longer suitable for use and is no longer in accordance with the function of the building. The application of High Tech Architecture in conservation buildings is generally not solid but the application of High Tech Architecture at Titi Papan Station will be designed as o Revitalization, Railway Station, High Tech Architecture ne unit but does not eliminate the historical value of cultural heritage buildings. The use of new materials at the station with the aim of following the development of increasingly advanced technology but still applying patterns to the old building of Titi Papan Station so that the identity of the building is not lost